[Wielkanocna karta okolicznościowa z pisanką i uszami] . Easter greeting card with an Easter egg and ears - Poczta Świąteczna NPP, NZS PW, TKZ "S" GSR. (Poczta Świąteczna NPP, 1988)
Blue and red print on white paper, with undivided back. Stamp contains two graphic images. First represents a Eastern egg with big red ears (allusion to Jerzy Urban) and caption "Happy eggs". Second represents the logo of the Gdańsk Repair Shipyard. Price: 50 zł per stamp.